(untitled) (Eastern Journal of Medical Sciences, 2017)
Malpositioned IUCD is a condition where, although the IUD is present within the uterine cavity, its placement is eccentric, usuallypresents with symptoms of pain and discharge or contraception failure. It is diagnosed by ultrasonography. Karmans cannula is ahollow plastic sheath used generally for endometrial biopsy and suction evacuation operations. The distal end if cut can be used tofit the intrauterine contraceptive device (IUCD) vertical limb and pushed up in the uterus to correct position. This is an easy andcost-effective way to reposition a low lying IUCD.